A case of inclusion body myositis with benign monoclonal gammopathy successfully responding to repeated immunoabsorption. Issue 2 (1st February 2000) - Nakayama, T; Horiuchi, E; Watanabe, T; Murayama, S; Nakase, H
Abstract : A 69 year old woman with inclusion body myositis is described. She presented with benign monoclonal gammopathy. She was resistant to steroid therapy, but responded to repeated immunoabsorption. Up to now, there has been no established therapy for inclusion body myositis, including IVIg. It is suggested that immunoabsorption could be an alternative therapy for inclusion body myositis, when it was accompanied by immunological abnormality.